2015
DOI: 10.1021/acschembio.5b00378
|View full text |Cite
|
Sign up to set email alerts
|

DNA Encoded Library Selections and Insights Provided by Computational Simulations

Abstract: DNA encoded library (DEL) technology allows for rapid generation of extremely large numbers of small molecules and is often used to find novel chemical starting points for pharmaceutically relevant proteins. DEL selection output consists of a list of small-molecule structures and enrichment levels. It is widely presumed that molecules with greater enrichment will have larger equilibrium association constants, and follow-up efforts are triaged accordingly. Herein we describe a simple mathematical model used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
84
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 24 publications
2
84
0
Order By: Relevance
“…As this ratio becomes much greater than 1, significant enrichment becomes difficult to achieve with solid-phase selections without incurring dramatic losses of ligands. 41 Since DNA-encoded libraries are an expensive resource, minimizing the amount used is desirable.…”
Section: Resultsmentioning
confidence: 99%
“…As this ratio becomes much greater than 1, significant enrichment becomes difficult to achieve with solid-phase selections without incurring dramatic losses of ligands. 41 Since DNA-encoded libraries are an expensive resource, minimizing the amount used is desirable.…”
Section: Resultsmentioning
confidence: 99%
“…On one hand, quantitative PCR methodologies provide direct experimental evidence regarding the efficiency and selectivity of ligand recovery [42,50]. Alternatively, certain estimates can be performed, using a computational analysis of selection results [51,52]. Many experimental factors may influence screening performance.…”
Section: Solution-phase Selectionsmentioning
confidence: 99%
“…Many experimental factors may influence screening performance. In addition to ligand affinity, the practical implementation of capture methodologies [51] and washing conditions [32] can have a profound impact on experimental results (e.g., enrichment factors and reproducibility) [53].…”
Section: Solution-phase Selectionsmentioning
confidence: 99%
“…We developed a mathematical model in which the presence (1) or absence (0) of each of the remaining 44 codons was represented by a binary digit in a 44-digit binary string, which was divided into three sub-strings corresponding to each codon group. Each of the possible binary sub-strings (2 11 , 2 10 , and 2 23 sub-strings for codon group 1, 2, and 3 respectively) representing a candidate set of viable codons was scored computationally using the annealing factor table to identify the number of incompatible sequence pairs contained within each codon set (see Supplementary Fig. 1 for details).…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, these approaches enable the construction of libraries with vast theoretical sizes exceeding millions or even billions of compounds, with the trade-off that as library size increases, the fraction of the library components that can be confirmed to undergo anticipated reaction pathways decreases. Importantly, the quality of a DNA-encoded library is determined by the proportion of properly synthesized molecules that are correctly encoded by their DNA tags, and model studies demonstrated that library quality directly affects the reliability of selections results 23, 24 . In most cases, purification of products after each chemical coupling step is not viable, which results in truncated byproducts linked to DNA tags that contaminate or even dominate the finished library 9 .…”
mentioning
confidence: 99%